Breastfeeding knowledge and attitudes of Nigerian mothers assessed by the Iowa infant feeding attitudes scale - Ezechi, Lilian O.; Otobo, Victoria; Mbah, Patricia E.; Ezechi, Oliver C. (International Journal Of Community Medicine And Public Health, 2021)
Background: Excusive breastfeeding practice in Nigeria is reportedly dwindling, yet the current breastfeeding practices and challenges remain largely unknown. To use the Iowa infant feeding attitude scale (IIFAS) to assess the breastfeeding knowledge and attitude of recently delivered mothers in Lagos Nigeria. Methods: A community-based survey. Study-related data were obtained from 636 mothers selected through multistage sampling, using IIFAS. The scale was validated for our environment before use in the study. The study data were managed with SPSS version 22.0. Results: The prevalence of any breastfeeding, exclusive breastfeeding at 6 months and timely initiation of breastfeeding was 99.5%, 22.2% and 47.4% respectively. While the mothers had some knowledge of breastfeeding, their overall knowledge and attitudes about breastfeeding were positive towards infant formula than breastfeeding. More than half of the mothers in our study stated that infant formula was as healthy for infants as breastmilk (62.3%), formula feeding is the better choice if the mother plans to go back to work (80.7%), and that formula feeding was more convenient than breastfeeding (56.9%). Previous exclusive breastfeeding experience (OR 2.7, 95% CI: 1.15, 8.41), being a housewife (OR 1.6, 95% CI: 1.14, 10.9), and having a positive attitude to breastfeeding (OR 1.9, 95% CI: 1.3, 11.6) were found to be associated with exclusive breastfeeding. Conclusions: Although breastfeeding was almost universal in the study area (99.5%), the knowledge and attitude to exclusive breastfeeding (EBF) were suboptimal. Public health education on breastfeeding should be intensified before, during and after pregnancy to improve mother’s EBF knowledge and attitude.